مخيلة الحرب فى الشعر العراقي بعد 2003 - كامل، عبدالهادي حسين; الحمداني، إياد عبدالودود عثمان (بعقوبة, 2020)
The war Fancy is one of the new adoptions adopted by this study regarding the period after 2003, and its political, social and psychological implications, accompanied by a major change in the level of acceptance, perception and awareness. This study represented a bold attempt to enter the depth of Iraqi poetry. Fancy is one of the most important foundational pillars. On it the fictional system specialized in receiving war not as a phenomenon but as a topic within general themes, his speech appeared clearly in Iraqi poetry, if he differed in the reception after this period, then it became a war of fate, existence and an entity on which the life of the Iraqi was based. Which she represented, and at the same time this study is the first of its kind to receive and work on this term (Fancy). However, most academic studies in general that approach the same proposition did not attempt to comprehend the Fancy and its function, but rather studied war as a general topic, for example (intertextuality in war poetry by Muhammad Abd al-Mawjid al- Badrani at the University of Mosul, the place in war poetry by Muhammad Sadiq Juma and the poetic image in his poem War 1980-2000 by Wahida Hassan), and these studies did not serve research as much as they did not rely on fancy as theorizing and establishing in its body. If the study finds it necessary for the introduction to focus on clarifying the concept of fancy as a term that has its own peculiarities in use, if we notice it clearly absent, then the role of Arabic dictionaries and foreign sources in the disclosure and presentation of it occurs. The first chapter dealt with the originality of the fancy - a theoretical introduction, and it came on four axes: The first axis of the fancy in Greek and Arab thought, which presented the philosophical ideas surrounding the fancy as a basic part of the subconscious mind based on the opinions of the ancients of the Arabs and others in the investigation and the second axis of the imagined in the rhetorical lesson Al-Qadim, which was adopted by the two important theorists, Abd al-Qaher al-Jarjani (474 AH) and Hazem al-Carthagini (684 AH) as an area capable of being compatible with the fictional system in their studies, And the third axis, fancy in the Western and Arab views, the first vision was accompanied by Samuel Taylor Coleridge when he disclosed the primary / primary and secondary imagination in poetry, and then the visions of Yassin Al-Nusayr when he researched the effects of fancy and place, and the fourth axis is the idiomatic (rhetorical) interference with Fiction, imagining, Imagined and illusion Dreaming is like a hidden instinctive feeling that the planned figure at the end of the chapter separates the subject matter of each term.
The second chapter dealt with the spatial fancy - and the techniques of the fancy, where it came on an introduction and two papers, the introduction specialized in the repercussions of war, the consequences of any war and a general historical perspective from antiquity to the manifestations of the war in the Iraqi poetic discourse, and the first topic (spatial fancy) if it turns out to us, that The Arab fancies in a General Perspective is a spatial fancy par excellence through the theories mentioned in the folds of this topic, believing in the role played by the mythological, historical and popular / local place. The third chapter came to discuss the critical approach, as it included an introduction to the phenomenon of revitalization after 2003, which adopted the absence of this phenomenon in criticism as a result of the societal fragments that stormed Iraq after the aforementioned period, and it came on four axes, the first axis in the artistic fancybased on a group of artists within The poetic text, the second axis, the intellectual fancy, which adopted intellectual visions, and the third axis the psychological / social fancy that brought together all phenomena as the fate of the Iraqi poet in fancy war, such as anxiety and alienation, and the fourth axis in employing rhythm in imagining where the rhythmic phenomena and their implications in the reception process. The research relied on a large group of Arab and foreign translated sources, primarily critical and rhetorical sources, and sources specialized in philosophy, psychology, sociology, and Iraqi poetry groups. The study reached the most important result, which is that the imagination is a philosophical and rhetorical term that must take its place compared to the term fictional system, and the term itself is not limited to war only, but can go out to other topics and phenomena, whether in Iraqi or Arabic poetry.
Keywords: الأدب العربي -- الشعر العربي -- الحروب العسكرية -- المخيلة الأدبية -- النقد الأدبي